Penerapan Teknik Token Ekonomi Untuk Mengurangi Perilaku Agresif Siswa di SMA Cokroaminoto Tamalanrea Makassar - Ibrahim, Herdiyanti (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2023)
The purpose of this study was to find out 1) a description of the aggressi behavior of students at SMA Cokroaminoto Tamalanrea Makassar 2) an overview of the implementation of token economy counseling to reduce student aggression behavior at SMA Cokroaminoto Tamalanrea Makassar 3) The token economy technique reduces the aggressive behavior of students at SMA Cokroaminoto Tamalanrea Makassar. This study used quantitative research with a single subject experimental research type. The subjects of this study were 2 students, who were determined by the target behavior which was measured continuously. Data analysis in this study used descriptive analysis and visual analysis. The results of this study indicate that the level of aggressive behavior of BL and S students before being given treatment is in the high category and after being given treatment is in the low category. 2) The application of economic token strategies for students encompasses a total of seven phases. 3) Implementing the token economy method has the potential to decrease the hostile conduct exhibited by students enrolled at SMA Cokroaminoto Tamalanrea Makassar. Keywords: Token Economy: Aggressive Behavior